The Response of European Energy Prices to ECB Monetary Policy - TorrÃ³, HipÃ²lit (International Journal of Energy Economics and Policy, 2019)
To our knowledge, this paper is the first to discuss the response of European energy commodity prices to unexpected monetary policy surprises from the European Central Bank (ECB). Using the Rigobon (2003) identification through heteroscedasticity method, we find a significant and positive response during the crisis period for Brent and coal. Similar results are obtained by other authors for European financial assets in this period. This result reinforces the idea that during this period, financial assets and some commodities positively responded to conventional and unconventional expansionary monetary policy measures, increasing confidence about the survival of the European monetary union. The remaining European energy commodities (electricity, EUAs, and natural gas prices) seem to be unaffected by monetary policy actions. We think these results are of interest to those economic agents and institutions involved in European energy markets and are especially important for the European Central Bank in order to predict the consequences of its monetary policy on the inflation objective. Keywords: Monetary policy, European Central Bank, energy commodities JEL Classifications: C26, E58, G13, Q41 DOI: https://doi.org/10.32479/ijeep.7190